2016
DOI: 10.1016/j.jcot.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of post-operative analgesia comparing suprascapular nerve block and interscalene brachial plexus block in patients undergoing shoulder arthroscopic surgery

Abstract: Suprascapular nerve blockInterscalene block Anaesthesia Post-operative analgesia a b s t r a c t Background: Shoulder arthroscopic surgeries have a high incidence of severe post-operative pain significant enough to interfere with recovery and rehabilitation. A regional anaesthetic technique combined with general anaesthesia reduces intra-operative requirements of anaesthesia and provides a better post-operative pain relief. As the commonly employed technique of interscalene brachial plexus block (ISB) is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
(27 reference statements)
0
28
1
2
Order By: Relevance
“…Many studies have confirmed the efficacy of these two methods compared to control, intravenous patient-controlled analgesia (IV-PCA), and local anesthetic infiltration ( 5-7 , 11 , 16 ,). Although many studies have compared the analgesic efficacy of SSNB and ISNB ( 2 , 17 , 21 , 27 - 39 ), this is the first study to compare C-SSNB and S-ISNB with rebound pain at 6-12 h after surgery as a primary endpoint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have confirmed the efficacy of these two methods compared to control, intravenous patient-controlled analgesia (IV-PCA), and local anesthetic infiltration ( 5-7 , 11 , 16 ,). Although many studies have compared the analgesic efficacy of SSNB and ISNB ( 2 , 17 , 21 , 27 - 39 ), this is the first study to compare C-SSNB and S-ISNB with rebound pain at 6-12 h after surgery as a primary endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a catheter for SSNB has been reported in arthroscopic surgery ( 18 , 45 ). Although the optimal dose needs to be verified in the future, a continuous dose of 2 mL per hour was sufficient to cover the small space in the scapular notch ( 2 ). As expected, C-SSNB resulted in a gradual decrease in the pain score over time and provided effective analgesia for at least 24 h after the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suprascapular nerve can be anesthetized using an anterior37 or posterior38 approach. Randomized trials conducted prior to 2017 have consistently found that, compared with ISB, suprascapular blocks result in higher pain scores in the immediate postoperative period (0–4 hours) 39–41. In contrast, all trials published since 2017 have concluded that suprascapular nerve blocks and ISBs provide similar analgesia and breakthrough analgesic consumption for arthroscopic16 29 as well as open20 shoulder surgery.…”
Section: Current Understanding Of Diaphragm-sparing Nerve Blocksmentioning
confidence: 99%
“…suprascapular nerve block [5,6], a single interscalene block combined with a continuous intrabursal infusion [7], intraarticular [8,9] or subacromial [10] injection of local anaesthetics, or postoperative intravenous opioid administration with patient-controlled intravenous analgesia [11]. There have been attempts to prolong the duration of sensory block by adding different adjuvants to local anaesthetics used in interscalene brachial plexus block (IBPB), such as dexamethasone [12,13] or dexmedetomidine [14].…”
mentioning
confidence: 99%